Dafina : hazina ya kiswahili - Al Habsy, Abdullah Salim Seif, 1936- (2012)
A collection of proverbs, sayings and idioms.
In Swahili.
Keywords: Proverbs, Swahili; Swahili language -- Figures of speech; Swahili language -- Idioms; Swahili language -- Terms and phrases